THE IMPACT OF USING MINDOMO ON HIGH SCHOOL STUDENTS' ANALYTICAL EXPOSITION TEXTS - Nida Aida Fitriya; Eva Rahmawati (International Journal of Research on English Teaching and Applied Linguistics, 2025)
Students often experience difficulties in writing analytical exposition text, especially in conveying their thoughts in a coherent and organized form. To address this problem, Mindomo was implemented to help students organize their writing. This research aims to find out the impact of using Mindomo as a digital mind mapping tool on high school students’ analytical exposition text writing by conducting quasi-experimental research. The implementation focused on two 10th grade classes of a Public Islamic High School in Ngawi, divided into one control class and one experimental class consisting of 30 students each. Each class underwent five sessions, starting with a pre-test, then the experimental class underwent treatment using Mindomo while the control class underwent learning using manual mind mapping, and ended with a post-test. The result shows experimental class's average post-test score increased to 83.79 after Mindomo implementation, up from a pre-test average of 75.20. Despite this gain, the hypothesis test (0.801) indicated no statistically significant difference between the control and experimental classes. This study found new information that the use of Mindomo in writing analytical exposition text in 10th grade has insignificant results.